Empreendimentos de economia solidária : alternativas de organização no mundo do trabalho (Chapecó, 1990-2010) - Fiore, Sedenir (2014)
This study investigates social relations of work that develop within the solidarity economy entrepreneurships, located in the city of Chapecó, between the years 1990 and 2010.This research analyses if the solidarity economy entrepreneurships. Are significant within the socioeconomic context Chapecó for the construction of new forms of work organization in the proposed period. The problem that guided the course of this investigation may be proposed as well as these developments to principles of solidarity economy are effected in the studied projects? The hypothesis is that the forms of work organization present in joint ventures are distant from those identified in the traditional capitalist enterprises, not as a new economic logic, but with elements that characterize like alternatives. The research was organized in three chapters. At first it was historically contextualized socioeconomic formation City Chapecó, dealing with major issues of economic development and the formation of the agro industry park city then was presented, based on the reading of the relevant literature, the main features of the organization of work in industries Sadia S/A and Aurora currently BRF foods, using these as comparative with those analyzed in the projects of solidarity economy models. Secondly, we analyzed the forms of organization of work within the solidarity economy entrepreneurships through the characterization of labor relations inherent solidarity City businesses Chapecó, with the initial timeline the early years of the 1990s. The third chapter did to the presentation of the results of empirical research in two joint ventures city's economy Chapecó in order to analyze the main features of social organization of observable work with in these developments and the consistency or inconsistency with the theory proposed by the thinkers of the solidarity economy. In methodological terms, we chose to reflect that combines theoretical, elements from the literature and empirical analysis, taken from the study of the proposed developments. The results confirm the hypothesis, and the forms of organization of work within the solidarity economy entrepreneurships. Move away from the forms of organization of agro industry in Chapecó because solidarity economy entrepreneurships. Instead of competition, management of the collective instead of individualism, the value of life to the simple reproduction of capital